9514 1404 393
Answer:
y = -3x +6
Explanation:
The perpendicular line will have the coefficients of x and y swapped (and one of them negated), and will have a constant appropriate to the point the line needs to go through.
The equation will look like ...
x -3y = 3 . . . . . . . . . . . . . given line
3x +y = constant . . . . . . perpendicular line
where "constant" can be found by substituting for x and y.
3x +y = 3(5) +(-9)
3x +y = 6 . . . . equation in standard form
To put this in slope-intercept form subtract 3x:
y = -3x +6